A Review of Water Quality Factors that Affect Nickel Bioavailability to Aquatic Organisms: Refinement of the Biotic Ligand Model for Nickel in Acute and Chronic Exposures. (13th July 2021) - Santore, Robert C.; Croteau, Kelly; Ryan, Adam C.; Schlekat, Christian; Middleton, Elizabeth; Garman, Emily; Hoang, Tham
Abstract: A review of nickel (Ni) toxicity to aquatic organisms was conducted to determine the primary water quality factors that affect Ni toxicity and to provide information for the development and testing of a biotic ligand model (BLM) for Ni. Acute and chronic data for 66 aquatic species were compiled for the present review. The present review found that dissolved organic carbon (DOC) and hardness act as toxicity‐modifying factors (TMFs) because they reduced Ni toxicity to fish and aquatic invertebrates, and these effects were consistent in acute and chronic exposures. The effects of pH on Ni toxicity were inconsistent, and for most organisms there was either no effect of pH or, in some cases, a reduction in toxicity at low pH. There appears to be a unique pH effect on Ceriodaphnia dubia that results in increased toxicity at pHs above 8, but otherwise the effects of TMFs were consistent enough across all organisms and endpoints that a single set of parameters in the Ni BLM worked well with all acute and chronic toxicity data for fish, amphibians, aquatic invertebrates, and aquatic plants and algae. The unique effects of pH on C. dubia may be due to mixture toxicity involving both Ni and bicarbonate. The implications of this mixture effect on BLM modeling and a proposed set of BLM parameters for C. dubia are addressed in the review. Other than this exception, the Ni BLM with a single set of parameters could successfully predict toxicity to all acute and chronic data compiled in the present review. Environ Toxicol Chem 2021;40:2121–2134. © 2021 SETAC